Adipose tissue oxylipin profiles vary by anatomical site and are altered by dietary linoleic acid in rats. (February 2019) - Cayer, Lucien G.J.; Mendonça, Anne M.; Pauls, Samantha D.; Winter, Tanja; Leng, Shan; Taylor, Carla G.; Zahradka, Peter; Aukema, Harold M.
Highlights: Oxylipin profiles of four rat adipose depots were determined. Depots differed in 20–22 carbon oxylipins from cytochrome P450 and cyclooxygenase. Linoleic acid derived lipoxygenase products made up the majority of oxylipin mass. Dietary linoleic acid increased n-6 PUFA derived oxylipins. Dietary linoleic acid with α-linolenic acid reduced n-6 PUFA oxylipins to control. Abstract: Dietary PUFA and their effects on adipose tissue have been well studied, but oxylipins, the oxygenated metabolites of PUFA, have been sparsely studied in adipose tissue. To determine the oxylipin profile and to examine their potential importance in various adipose sites, female and male rats were provided control, high linoleic acid (LA), or high LA and high α-linolenic acid (LA + ALA) diets for six weeks. Analysis of gonadal (GAT), mesenteric (MAT), perirenal (PAT), and subcutaneous adipose tissues (SAT) revealed higher numbers of oxylipins in MAT and SAT, primarily due to 20–22 carbon cytochrome P450 oxylipins, as well as metabolites of cyclooxygenase derived oxylipins. LA oxylipins made up 75–96% of the total oxylipin mass and largely determined the total relative amounts between depots (GAT > MAT > PAT > SAT). However, when the two most abundant LA oxylipins (TriHOMEs) were excluded, MAT had the highest mass of oxylipins and exhibited the most sex differences. These differences existed despite comparable PUFA composition between depots. Dietary LA increased oxylipins derived from n-6 PUFA, and the addition of ALA generally returned n-6 PUFA oxylipins to levels similar to control and elevated some n-3 oxylipins. These data on oxylipin profiles in adipose depots from different anatomical sites and the effects of diet and sex provide fundamental knowledge that will aid future studies investigating the physiological effects of adipose tissue.